Posture Assessment and Ergonomic Analysis of Pot Makers - Ranjo, Baldhomero; Madariaga, Richard V. (JPAIR Multidisciplinary Research, 2008)
This study applied ergonomics principles to improve the work environment of pot makers in Barangay Nagrebcan, San Nicolas, Ilocos Norte. The objectives included assessing the posture of pot makers, conducting a task analysis of pot making, analyzing workstations, identifying workplace hazards, determining common work-related musculoskeletal disorders (WMSDs), and examining the relationship between demographic factors and WMSDs. A descriptive-correlation design was used, focusing on the value of ergonomics in this context. The study divided task analysis into three phases: mixing, kneading, and molding. It employed tools like the Rapid Entire Body Assessment (REBA), Ovako Working Posture Analysis System (OWAS), Workplace Hazard Assessment, and Discomfort Survey questionnaires. Findings revealed that pot makers often adopted awkward postures, such as deep squatting and trunk bending, which posed high risks of injury according to REBA and required corrective measures as indicated by OWAS. Workplace hazards included impact, dust, penetration, thermal, and rain exposure. Discomfort was commonly reported in the low back and wrist/hands. The study highlighted the need for ergonomic improvements to enhance productivity and employee welfare in the pottery industry of the Ilocos Region.